Student Innovation Performance: Underpinning Theories - Wu, Yongshun; Fernando, Yudi (International Journal of Innovation Research in Education, Technology and Management, 2024)
This study explores the relationship between extracurricular activities and student innovation performance, drawing on various theoretical frameworks and empirical evidence. Through a comprehensive literature review, the study examines the impact of extracurricular activities on students' development of critical thinking, creativity, communication, and collaboration skills—essential components of innovation. The TRIZ innovation theory and social cognitive career theory provide theoretical underpinnings for understanding how participation in extracurricular activities fosters innovation skills among students. Additionally, the study presents a literature review matrix summarizing key findings from previous research on extracurricular activities and their effects on student development. The findings suggest that participation in extracurricular activities significantly enhances students' capacity for innovation by cultivating higher-order thinking skills and providing opportunities for real-world problem-solving. Moreover, the study discusses the implications of extracurricular engagement for students' future career success and organizational innovation. The study concludes with recommendations for future research, emphasizing the need for comparative studies across diverse student populations, in-depth analyses of specific types of extracurricular activities, and exploration of cultural differences in attitudes toward extracurricular involvement. Overall, this study contributes to a better understanding of how extracurricular activities influence student innovation performance and provides insights for educators and policymakers seeking to enhance innovation capabilities among young professionals